The Effect of The Application of Media for Burnt Husks on the Growth of Mustard Plants (Brassica juncea L.) - Sriwani Lamasrin; Diane Pioh; Tommy Ogie (Sam Ratulangi University, 2023)
This study aims to find out how the effect of the application of planting media on the growth of roasted husks on the growth of Mustard Greens (Brassica Juncea L.) The planting medium is the main component when farming and must be adjusted to the type of plant to be planted. Soil is the main planting medium, but the development of science and technology has resulted in a variety of technological innovations for plant-growing media such as hydroponics and aquaponics as well as fuel husk growing media which is waste from former rice mills which is used as organic growing medium. Rice husk contains important chemical nutrients, namely 9.02% water content, 3.03% crude protein, 1.18% fat, 17.17% ash, and 33.71% basic carbohydrates (Nutani et al., 2020). When dealing with the increasing world of industry, adding roasted husks to the planting medium can be a solution for the cultivation of mustard greens. This study used a completely randomized design (RAL) with 5 (five) treatment levels with 4 (four) replications. Each experimental unit had one mustard plant seed and obtained 20 plants. The results showed that the application of roasted husk media had no significant effect on the growth of mustard plants. The addition of burnt husks and soil planting medium in treatments P0, P1, and P2 showed the highest growth results in plant height, number of leaves, leaf length, leaf width, number of leaves, fresh weight, and root length. Then in the P3 and P4 treatments, the results were low both plant height, leaf length, leaf width, number of leaves, and fresh weight. Keywords; Growing medium, Roasted Rice Husk, Mustard plants Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh aplikasi media tanam terhadap pertumbuhan tanam sekam bakar terhadap pertumbuhan Tanaman Sawi (Brassica Juncea L.) Media tanam merupakan komponen utama ketika bercocok tanam dan harus disesuaikan dengan jenis tanaman yang akan ditanam namun, perkembangan ilmu pengetahuan dan teknologi menghasilkan beragam inovasi media tanam diantaranya hidroponik, , aquaponik juga media tanam sekam bakar yang merupakan limbah hasil bekas gilingan padi yang dimanfaatkan sebagai media tanam organik. Sekam padi mengandung unsur hara kimia penting yaitu kadar air 9,02%, protein kasar 3,03%, lemak 1,18%, abu 17,17% dan karbohidrat dasar 33,71% (Nutani et al., 2020). Ketika berhadapan dengan makin meningkatnya dunian industry, maka dengan penambahan sekam bakar pada media tanam dapat menjadi salah satu solusi untuk budidaya tanam sawi. Penelitian ini menggunakan Rancangan acak lengkapa ( RAL) dengan 5 ( lima) taraf perlakuan dengan 4 (empat) ulangan. Setiap satuan percobaan memiliki satu bibit tanaman sawi dan diperoleh 20 tanaman. Hasil penelitian menunjukan bahwa Aplikasi media sekam bakar tidak berpengaruh nyata terhadap pertumbuhan tanaman sawi. Penambahan sekam bakar dan media tanam tanah pada perlakuan P0, P1 dan P2 menunjukan hasil pertumbuhan tinggi tanaman, jumlah daun, panjang daun, lebar daun, banyak daun, bobo berat segar dan panjang akar tertinggi. Kemudian pada perlakuan P3 dan P4 diperoleh hasil yang rendah baik tinggi tanaman, panjang daun, lebar daun, banyak daun dan bobot berat segar. Kata Kunci : Media Tanam, Sekam Bakar, Tanaman Sawi